2003
DOI: 10.1160/th03-03-0145
|View full text |Cite
|
Sign up to set email alerts
|

Duration of exposure to high fluid shear stress is critical in shear-induced platelet activation-aggregation

Abstract: Platelet functions are increasingly measured under flow conditions to account for blood hydrodynamic effects. Typically, these studies involve exposing platelets to high shear stress for periods significantly longer than would occur in vivo. In the current study, we demonstrate that the platelet response to high shear depends on the duration of shear exposure. In response to a 100 dyn/cm2 shear stress for periods less than 10-20 sec, platelets in PRP or washed platelets were aggregated, but minimally activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Platelets in platelet-rich plasma (PRP) sheared at 20 dynes/cm 2 for 60 seconds showed approximately 3% activation, as measured by CD62P expression. 40 This value is higher than the 1.65% to 1.67% activation for the 5-minute samples in our T1 = 0 seconds waveform experiments, which shows that constant shear stress yields higher activation values than variable shear stress, where platelets are exposed to a higher value for only a fraction of the total exposure time. Furthermore, platelets in whole blood exposed to a constant shear rate 420 s −1 (corresponding to a shear stress of 14.7 dynes/cm 2 , assuming whole blood viscosity of 3.5 cP) did not express a significant increase in GP IIb/IIIa activation (approximately 1%) at 4.5 minutes, whereas Annexin V binding was detected to be 1.5% to 2%.…”
Section: Discussionmentioning
confidence: 48%
“…Platelets in platelet-rich plasma (PRP) sheared at 20 dynes/cm 2 for 60 seconds showed approximately 3% activation, as measured by CD62P expression. 40 This value is higher than the 1.65% to 1.67% activation for the 5-minute samples in our T1 = 0 seconds waveform experiments, which shows that constant shear stress yields higher activation values than variable shear stress, where platelets are exposed to a higher value for only a fraction of the total exposure time. Furthermore, platelets in whole blood exposed to a constant shear rate 420 s −1 (corresponding to a shear stress of 14.7 dynes/cm 2 , assuming whole blood viscosity of 3.5 cP) did not express a significant increase in GP IIb/IIIa activation (approximately 1%) at 4.5 minutes, whereas Annexin V binding was detected to be 1.5% to 2%.…”
Section: Discussionmentioning
confidence: 48%
“…A useful measure for the variable wall shear rate to which platelets are exposed is the integral shear history, i.e., the product of shear rate and exposure time (23). A reported threshold of the integral shear history for platelet aggregation in response to constant shear is 50 Pa·s (24).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular components of blood (-46% of the volume in human blood) consist primarily of red blood cells (RBCs) (or erythrocytes) (-98% in cell number), which may stimulate blood clot formation upon release of an intracellular aggregation agonist (i.e. ADP) (12). The remaining 2% of the cellular phase consists primarily of white blood cells (WBCs) (or leukocytes) and platelets (5, 13), which play major roles in immune and thrombotic processes, respectively.…”
Section: Human Platelet Backgroundmentioning
confidence: 99%
“…This supposition was repeatedly discredited by several studies, namely those using rotational viscometer systems (56,12) that found that platelet activation depends on the presence of vWF and functional platelet glycoprotein complexes GP Ib-IX-V and GP Ilb-IIIa in conjunction with moderate shear stress magnitudes (26,59). This connection between rheologic and vascular factors is supported by the fact that mixing vWF with platelets in a static or stirred suspension will fail to generate a platelet response (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation